A Dual-Surgeon Approach to Breast Cancer Surgery in a Transmale. Issue 6 (December 2021) - Parmeshwar, Nisha; Alcon, Andre; Kim, Esther A.
Abstract : Abstract: With increasing numbers of gender-affirming chest surgery, new questions regarding breast cancer management and surgical practice arise. Guided by our case report, we present a comprehensive review of breast cancer surgery in a transman to educate both plastic and breast surgeons on various factors to consider when caring for these patients. Our case involves a 31-year-old transmale patient who presented for plastic surgery consultation for gender-affirming mastectomy but was subsequently found to have a right breast mass. This is the first case in the literature of a transmale on hormone therapy with breast cancer interested in gender-affirming surgery, thus requiring a dual-surgeon approach for oncologic and gender-affirming mastectomy. With a multidisciplinary patient-centered approach involving breast surgery, plastic surgery, medical oncology, and radiology, we devised a surgical plan to safely remove his breast tissue with consideration for his gender-affirming goals. He underwent a right skin-sparing mastectomy with sentinel node biopsy and left prophylactic skin-sparing mastectomy through skin markings by the plastic surgeon, with bilateral free nipple grafts. Final pathology confirmed estrogen and progesterone receptor–positive and androgen receptor–positive invasive ductal carcinoma with clear margins and negative sentinel node. The patient did not require adjuvant chemotherapy or radiation but was started on adjuvant hormone therapy targeting his hormone receptor positive cancer. He elected to stay on low-dose masculinizing hormone therapy with continued surveillance examinations. We follow our case with a review of the current literature involving breast cancer in transmales to explore current screening practices, surgical recommendations, adjuvant therapies, continuation of masculinizing hormone therapy, and postoperative surveillance guidelines in the hopes of informing plastic surgeons in having these discussions with their transmale patients and thus improving informed cancer care for this population.